ENERGY POLICY REFORM AND RURAL POVERTY: A REVIEW OF THE IMPACT OF PETROLEUM SUBSIDY REMOVAL ON NIGERIAN FARMERS (AUN INTERNATIONAL CONFERENCE, 2025)
Petroleum subsidy in Nigeria was introduced to stabilize fuel prices and protect consumers from global market fluctuations. Over time, the policy became fiscally unsustainable, consuming significant public resources and encouraging inefficiency and corruption. The removal of the subsidy was implemented to promote fiscal stability, improve market efficiency, and redirect savings to development programs. However, the reform has imposed severe hardship on rural farmers who rely on fuel for irrigation, mechanized farming, and transportation. Higher fuel prices have increased production costs, reduced farm profitability, and deepened rural poverty. Evidence from existing studies shows that while subsidy removal improved fiscal transparency, it worsened welfare conditions due to weak social protection and poor program targeting. The findings highlight disparities between rural and urban households and limited access to affordable energy alternatives. Policy responses should focus on promoting equitable energy access, supporting agricultural productivity, and strengthening livelihood resilience to ensure that fiscal reforms foster inclusive and sustainable rural development in Nigeria.